Biomass production, yield and quality response of spring wheat to soil tillage, crop rotation and nitrogen fertilisation in the Swartland wheat producing area of South Africa - Maali, Safiah Hasan (Stellenbosch : University of Stellenbosch, 2010)
Thesis (PhD(Agric) (Agronomy))--University of Stellenbosch, 2003.